Improvement of ship stability and safety in damaged condition through operational measures: Challenges and opportunities. (1st August 2016) - Boulougouris, Evangelos; Cichowicz, Jakub; Jasionowski, Andrzej; Konovessis, Dimitris
Abstract: Guaranteeing a sufficient level of safety from the point of view of stability is typically considered to be a matter of design. The overall level of safety of a ship, however, can only be guaranteed when considering passive design measures in conjunction with active operational measures, in a holistic, balanced and cost-effective manner. Time could therefore be coming for systematically considering operational measures as a recognised and normed integral part of a holistic approach to ship safety from the point of view of stability. In this respect, the scope of this paper is to identify open challenges and to provide, in general, food for thought for stimulating a discussion on the topic of operational measures, with specific attention to the damaged ship condition. The aim is to provide ground for further proceeding towards the goal of implementing a virtuous integrated approach to ship stability safety which gives due credit to effective and robust operational risk control options. Highlights: Operational measures to be considered in conjunction with typical design measures for increased ship safety. Systematically considering operational measures as an integral part of a holistic approach to ship safety. Damaged ship condition is addressed. Current-state-of-affairs, opportunities and challenges are discussed.